Indikator sikap karakter disiplin siswa berbasis hadis-hadis Bukhari dan hierarkinya menurut Wali Kelas SDIT di Jakarta - Andriana, Nesia; Hafidhuddin, Didin; Mujahidin, Endin (Ta'dibuna: Jurnal Pendidikan Islam, 2021)
The formation of disciplined character is one of the important aspects in primary education. This study aims to formulate attitude indicators taken from disciplined character education that is based on Bukhari ahí¢dí®th and to explore the perceptions of homeroom teachers at SDIT in Jakarta on these attitude indicators. This research is a mixed study with a literature study approach and an analytic network process approach. The indicators of discipline character attitudes that are formulated are obeying, being responsible, not bullying, and being polite. The homeroom teachers have the opinion that the most significant variables as indicators, are obedience (0.33), responsibility (0.27), respect and courtesy (0.21), and not bullying (0.11). Abstrak Pembentukan karakter disiplin salah satu aspek penting dalam pendidikan dasar. Penelitian ini bertujuan untuk merumuskan indikator sikap hasil pendidikan karakter disiplin dari hadis-hadis Bukhari serta menggali persepsi wali kelas SDIT di Jakarta atas indikator sikap tersebut. Penelitian ini adalah penelitian campuran dengan pendekatan studi pustaka serta pendekatan analytic network process. Indikator sikap karakter disiplin yang terumuskan adalah taat, bertanggung jawab, tidak merundung dan bersikap santun. Para wali kelas berpendapat bahwa variabel yang paling signifikan sebagai indikator secara berturut-turut adalah sikap taat (0,33), bertanggung jawab (0,27), hormat dan santun (0,21) dan tidak merundung (0,11).